Adjuvant chemotherapy for a T3 additional tumor nodule in the same lobe: ready for prime time? - Latif, M. Jawad; Jones, David R. (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
In a recent edition of the Journal of Thoracic Oncology, Salazar et al. sought to determine the role of adjuvant chemotherapy in a subgroup of patients with T3 non-small cell lung cancer (NSCLC) who presented with an additional tumor nodule in the same lobe (1). To address this question, the authors used the National Cancer Database (NCDB), which, in 2010, added an additional subcategory to identify T3 tumors on the basis of the presence of an additional tumor nodule in the same lobe. From this cohort of patients with T3 tumors (n=1,013), those requiring additional chemotherapy for other indications—such as lymph node metastases, tumors ≥4 cm, and direct chest wall invasion—were excluded.